2018
DOI: 10.3390/molecules23061327
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antioxidant Activity of Bioactives in Colored Grains by Nano-Carriers in Human Lens Epithelial Cells

Abstract: The use of phytochemicals for preventing chronic diseases associated with oxidative stress such as cataracts is hindered by their low bioavailability. The effects of nano-carriers on the antioxidant activities of extracts of black rice with giant embryo (BRGEx) and soybeans (SBx) have been determined in human lens epithelial B3 cells. Scanning (SEM) and transmission electron microscopy (TEM) demonstrated that rGO (reduced graphene oxide) has a flat surface unlike GO (graphene oxide), which has a distinctive wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The antioxidant activity of GBN lies in the scavenging of hydroxyl and superoxide radicals. In was observed that few-/multi-layer GR is more active than GO, despite its lower surface area, suggesting that the main scavenging activity is associated with pristine sp 2 carbon domains on basal surfaces, rather than with H-donation from hydroxyl or hydroquinone groups [ 117 , 118 ]. Thus, GBNs can protect various biomolecular target molecules from oxidation.…”
Section: Gbns As Drugs and Nanocarriersmentioning
confidence: 99%
“…The antioxidant activity of GBN lies in the scavenging of hydroxyl and superoxide radicals. In was observed that few-/multi-layer GR is more active than GO, despite its lower surface area, suggesting that the main scavenging activity is associated with pristine sp 2 carbon domains on basal surfaces, rather than with H-donation from hydroxyl or hydroquinone groups [ 117 , 118 ]. Thus, GBNs can protect various biomolecular target molecules from oxidation.…”
Section: Gbns As Drugs and Nanocarriersmentioning
confidence: 99%
“…The [31]. The formation of the radical adduct at the sp 2 carbon sites determines the antioxidant activity of carbonaceous nanomaterials.…”
Section: Anti-oxidant Assaysmentioning
confidence: 99%
“…Recent reports have demonstrated that several types of nanoparticles act as potent free radical scavengers and antioxidants [22,23]. The prepared nanocomposites GO and ZnO-rGO were investigated for anti-oxidant properties using DPPH radical and H 2 O 2 scavenging assays.…”
Section: Antioxidant Assaysmentioning
confidence: 99%
“…The antioxidant activity pattern can depend on the structure of graphene oxide or few-layer graphene [25]. Some researchers proposed that antioxidant propriety of carbon materials may involve radical adduct formation at sp2 carbon sites, which delocalizes spin across the conjugated graphene backbone and leads to the destruction of the radical following second adduct formation, through electron transfer, through hydrogen donation from functional groups, or through chelation of transitional metal ions and inhibition of Fenton-based radical generation [23,24]. Interestingly, GO showed a more considerable scavenging efficiency using the DPPH radical test while the ZnO decorated GO was more efficient in the H 2 O 2 antioxidant assays.…”
Section: Antioxidant Assaysmentioning
confidence: 99%